Multicriteria analysis as a method for engaging stakeholders and citizens in activities aimed at supporting climate resilience and adaptation to climate change – Gdansk Coastal City Living Lab case study - Barańczuk Jacek; Masik Grzegorz; Barańczuk Katarzyna; Meulenberg Cécil J.W. (Miscellanea Geographica: Regional Studies on Development, 2024)
In this study, we aimed to present solutions to mitigate the effects of climate change, summer torrential rain, and pluvial flooding. Within the Gdańsk living lab, a multicriteria analysis (MCA) was performed to assess the implementation of ecosystem-based adaptation (EBA) options for the city of Gdańsk. The results show an assessment of the stakeholders’ acceptability and local knowledge of selected EBA options including rainwater gardens, water parks, retention ponds, green roofs, green walls, community gardens, urban farming and tree plantation. All the proposed EBAs were generally accepted during an online living lab stakeholder meeting. However, EBA solutions that were less intrusive on the natural landscape were preferred over large structures. Yet during the consecutive physical workshop with identified stakeholder composition, there was a higher level of approval for large structures to reduce the level of flood risk, indicating that face-to-face meetings significantly influence the choice of measures during MCA procedures. This has highlighted the importance of physical meetings of MCA for selecting proper implementation options.